Impact of chronic obstructive pulmonary disease on linear and nonlinear dynamics of heart rate variability in patients with heart failure - Goulart,C.L. (2021)
The objective of this study was to investigate the impact of chronic obstructive pulmonary disease (COPD)-heart failure (HF) coexistence on linear and nonlinear dynamics of heart rate variability (HRV). Forty-one patients (14 with COPD-HF and 27 HF) were enrolled and underwent pulmonary function and echocardiography evaluation to confirm the clinical diagnosis. Heart rate (HR) and R-R intervals (iRR) were collected during active postural maneuver (APM) [supine (10 min) to orthostasis (10 min)], respiratory sinus arrhythmia maneuver (RSA-M) (4 min), and analysis of frequency domain, time domain, and nonlinear HRV. We found expected autonomic response during orthostatic changes with reduction of mean iRR, root mean square of successive differences between heart beats (RMSSD), RR tri index, and high-frequency [HF (nu)] and an increased mean HR, low-frequency [LF (nu)], and LF/HF (nu) compared with supine only in HF patients (P<0.05). Patients with COPD-HF coexistence did not respond to postural change. In addition, in the orthostatic position, higher HF nu and lower LF nu and LF/HF (nu) were observed in COPD-HF compared with HF patients. HF patients showed an opposite response during RSA-M, with increased sympathetic modulation (LF nu) and reduced parasympathetic modulation (HF nu) (P<0.05) compared with COPD-HF patients. COPD-HF directly influenced cardiac autonomic modulation during active postural change and controlled breathing, demonstrating an autonomic imbalance during sympathetic and parasympathetic maneuvers compared with isolated HF.